Pengaruh Job Engagement, Organization Engagement Terhadap Service Performance Dimediasi Oleh Job Satisfaction Pada Karyawan Resto Cepat Saji di Jakarta Pusat - Romadhania, Nurizahara; Berliyanti, Dita Oki (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2024)
The purpose of this study was to analyze the effect of job engagement and organization engagement on service performance mediated by job satisfaction. The survey produced 152 respondents. The methods used to analyze this research are, instrumental tests such as validity and reliability as well as hypothesis tests and sobel test using SPSS program analysis, SEM and Sobel test calculators. The results showed that job engagement has a positive effect on job satisfaction, job engagement has a negative effect on service performance, organization engagement has a positive effect on job satisfaction, organization engagement has a positive effect on service performance, job satisfaction has a positive effect on service performance, job engagement and organization engagement have a positive effect on service performance mediated by job satisfaction.